2015
DOI: 10.1007/s11803-015-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of safety evaluation system of buildings on a seismic field based on the network platform

Abstract: This paper describes a set of on-site earthquake safety evaluation systems for buildings, which were developed based on a network platform. The system embedded into the quantitative research results which were completed in accordance with the provisions from Post-earthquake Field Works, Part 2: Safety Assessment of Buildings, GB18208.2 -2001, and was further developed into an easy-to-use software platform. The system is aimed at allowing engineering professionals, civil engineeing technicists or earthquake-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The safety assessment system IADS 11 introduces quantitative evaluation; the disadvantage is that the safety assessment results of other structural types are not as accurate as those of masonry structures. These computer‐based safety assessment systems 13,14,16,47 can quickly calculate the overall seismic damage index of the masonry structure and the concrete structure, but the systems can only work in southwest China, not all of China or the world. Vidal et al 15 introduce two single and direct methods that use less timeframe and be easier to be applied, but the methods can only be used in small‐to‐medium size towns stricken by a damaging earthquake.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety assessment system IADS 11 introduces quantitative evaluation; the disadvantage is that the safety assessment results of other structural types are not as accurate as those of masonry structures. These computer‐based safety assessment systems 13,14,16,47 can quickly calculate the overall seismic damage index of the masonry structure and the concrete structure, but the systems can only work in southwest China, not all of China or the world. Vidal et al 15 introduce two single and direct methods that use less timeframe and be easier to be applied, but the methods can only be used in small‐to‐medium size towns stricken by a damaging earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…According to this criterion, a rapid safety assessment can be achieved through the safety assessment systems IASSAB V1.0 and IADS 10,11 . Several computer‐based safety assessment systems have been developed that can quickly calculate the overall seismic damage index 12–16,47 . Additionally, a method for safety assessment data acquisition for a seismically damaged building was introduced 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaking table test was also used to study the earthquake response of multi-story brick house in sandy soil foundation [3], and they demonstrated that: At low intensity, foundation failure contributed more to isolation on multi-story brick house than liquefaction, but at high intensity, it was contrast. According to the shaking table test, G.X.…”
Section: Introductionmentioning
confidence: 99%